Synthesis and characterization of polyvinyl alcoholcerium (III) acetate nanofiber composites of various ratio of [OH-]:[Ce3+] - Bryan Andrew, Balasan (2017)
This research describes the synthesis and characterization of Polyvinyl Alcohol/Cerium (III) Acetate nanofibers by electrospinning using different molar ratios (PVA/Ce(III)Ac). The molecular weight of PVA used was MW 145,000 and Cerium (III) Acetate Hydrate at 99.9% purity. 11wt% of PVA solution with different molar ratio were prepared. The prepared solutions were molar ratios of PVA:Ce(III)Ac as 1:0, 1:1/3, 1:1/2, and 1:1. Viscosity results showed that increasing Ce(III)Ac ratio have decreased the viscosity of the prepared solutions. The pure solution was spun into nanofiber having good flexibility. Nanofiber having increasing ratio of Ce(III)Ac becomes less flexibility and more breakable. Observation under microscope reveals that the nanofibers of 1:0 were smooth, aligned, continuous and average diameter 550 ± 181 nm. Nanofibers with increasing ratio of Ce(III)Ac showed increasing beads, random allignment nanofibers, discontinuous and average diameter of 168 ± 54 nm, 216 ± 74 nm and 186 ± 47 nm. Thermal gravimetric analysis showed that nanofiber with increasing Ce(III)Ac at second stage experienced greater weight lost compared to the second stage of pure PVA. Pure PVA nanofiber has high thermal stability because onset temperature of second stage was 199°C whereas nanofibers of increasing rato of Ce(III)Ac were 160°C-181°C. Differential scanning calorimetry results of first heating cycle showed similar first melting point and cold crystallization at 32°C and 36°C respectively. For the second heating cycle showed that melting point had increased for recrystallization of all nanofiber compoites samples at around 223 ± 2°C but cold crystallization have changed for increasing Ce(III)Ac at 320 ± 24°C. The second melting point after cold crystallization occurs much later as for increasing Ce(III)Ac ratios.